Oxyphor 2P: A High-Performance Probe for Deep-Tissue Longitudinal Oxygen Imaging - Esipova, Tatiana V. (Cell Metab, 2019)
Quantitative imaging of oxygen distributions in tissue can provide invaluable information about metabolism in normal and diseased states. Two-Photon Phosphorescence Lifetime Microscopy (2PLM) has been developed to perform measurements of oxygen in vivo with micron-scale resolution in 3D; however, the method’s potential has not yet been fully realized due to the limitations of current phosphorescent probes technology. Here we report a new sensor, Oxyphor 2P, which enables oxygen microscopy twice as deep (up to 600 μm below the tissue surface) and with ~60 times higher speed than previously possible. Oxyphor 2P allows longitudinal oxygen measurements without having to inject the probe directly into the imaged region. As proof-of-principle, we monitored oxygen dynamics for days following micro-stroke induced by occlusion of a single capillary in the mouse brain. Oxyphor 2P opens up new possibilities for studies of tissue metabolic states using 2PLM in a wide range of biomedical research areas.